THE ROLE OF TAX AVOIDANCE IN MODERATING THE RELATIONSHIP BETWEEN DEBT COVENANT, PROFITABILITY, AND TRANSFER PRICING - Firmansyah Firmansyah; Martinus Robert Hutauruk; Nadiya Yunan; Pilipus (Berkala Akuntansi dan Keuangan Indonesia, 2026)
Transfer pricing is an important concern in international accounting and taxation, acting as a mechanism to distribute profits affected internally by a company to facilitate tax avoidance strategies. Although transfer pricing is often studied as a tax avoidance tool, research gaps arise in the company's dilemma in shifting profits without violating debt covenants in order to maintain a balance between fiscal burden efficiency and creditor compliance. This quantitative study aims to empirically investigate how debt covenants and profitability impact transfer pricing decisions, with tax avoidance acting as a moderating factor, in manufacturing companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The purposive sampling method resulted in a total of 125 observations and, in the Moderate Regression Analysis (MRA), showed that debt agreements and profitability had a significant positive effect on transfer pricing policies. It was found that tax avoidance could not reduce the relationship between debt agreements and profitability on transfer pricing decisions, suggesting that contractual compliance motivation and financial performance were more influential than tax avoidance intentions in shaping a company's transfer pricing policy.